Biomass‐Derived 3D Carbon Aerogel with Carbon Shell‐Confined Binary Metallic Nanoparticles in CNTs as an Efficient Electrocatalyst for Microfluidic Direct Ethylene Glycol Fuel Cells. Issue 16 (4th March 2019) - Raj kumar, T.; Gnana kumar, G.; Manthiram, Arumugam
Abstract: Flexible and 3D carbon aerogels (CAs) composed of carbon nanotubes (CNTs) with carbon shell‐confined binary palladium–nickel (Pdx –Niy ) nanocatalysts on carbon fibers (Pdx –Niy /NSCNT/CA) have been developed through a facile chemical vapor deposition method. The 3D porous carbon network and the synergistic effect of carbon shell‐confined bimetal nanoparticles of rationally constructed aerogels facilitate enhanced electrocatalytic and antipoisoning activities toward ethylene glycol (EG) oxidation reaction compared to the commercial Pt/C catalyst. With the 3D morphological features and direct growth of Pd–Ni bimetallic nanoparticles encapsulated CNTs on carbon fibers, the Pd52 –Ni48 /NSCNT/CA delivers a maximum microfluidic direct ethylene glycol fuel cell (µDEGFC) power density and durability of, respectively, 62.8 mW cm −2 and 60 h. The superior performance observed, with Pd52 –Ni48 /NSCNT/CA amongst the catalysts reported in the literature, opens an exciting research avenue towards powering next‐generation, portable electronics. Abstract : A biomass derived 3D cotton aerogel with carbon shell‐confined Pd –Ni nanoparticles in carbon nanotubes is realized as a free‐standing, bendable anode for efficient ethylene glycol oxidation. The 3D porous structure facilitates ion/electron transport through a rapid diffusion of electrolyte and Pd–Ni nanoparticles in the tips of CNTs and catalytically activates the outer graphitic layers and promotes microfluidic direct ethylene glycol fuel cell performance.